روايات نجيب الكيلاني وشحنون أحمد الإسلامية بين النظرية والتطبيق : دراسة نقدية مقارنة - فابية تؤلوبوك @ حاج مامينج (al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2007)
This study investigates the backgrounds and the works of two prominent authors, NajÊb al KÊlÉni and Shahnon AÍmad from a comparative literature perspective. General literary theories and particularly Islamic literary theories are discussed in detail. The present research focuses on both authors’ novels written after they have introduced their own versions of Islamic literary theory. In order to establish the focus in the present research, emphasis is given to the creative components of both authors’ novels including plot, style and technique, characters, setting and time. Through these components, the study examines how the theories outlined by both novelists are applicable to their works. Since, each of them presented their own ideas of Islamic literature, both tried to apply the ideas in their literary works. The study subsequently highlights the Islamic values and creativity techniques as well as similarities and differences between both of them, in order to evaluate both authors’ literary works and the application of theories as outlined by them. The study shows that both of them are capable of applying their own theories except in a few aspects especially due to the human weaknesses. The perspective of Islamic values is better illuminated by NajÊb al KÊlÉni compared to the work of Shahnon AÍmad. Whereas Shahnon AÍmad has his own way of presenting his Islamic values in which he tends to satire his idea indirectly. Nevertheless, Shahnon AÍmad is without a doubt is the pioneer in paving the establishment of Islamic Literature, and he definitely deserves to be regarded the leader of Malaysian Islamic literature.